Hubungan Kondisi Geologi Terhadap Kondisi Massa Batuan dan Kestabilan pada Lubang Bukaan Tambang Bawah Tanah Kencana Menggunakan Rock Mass Rating dan Metode Elemen Hingga - Yunita Terania Sitepu; Daniel Radityo (Jurnal Ilmiah Geologi PANGEA, 2026)
Geological conditions at the Kencana underground mine, a low-sulfidation epithermal gold deposit with intensive structural control, strongly govern the rock mass characteristics and opening stability. The lithology at the study site consists of andesite lava and quartz veins controlled by north-south to northwest-southeast trending faults, with alteration intensity varying across openings. This study evaluates the relationship between these geological conditions and rock mass quality and stability at four openings (08H, 09E, 14D, and 00B) using the Rock Mass Rating (RMR) system and finite element method. Openings 08H and 14D, composed of andesite lava with propylitic alteration (chlorite and epidote), exhibit relatively preserved rock strength and are classified as fair rock. In contrast, 09E and 00B experienced intensive argillic alteration caused by acidic hydrothermal fluid interaction, converting primary minerals into soft, water-reactive clay minerals, resulting in poor rock classification with the shortest stand-up time and largest roof load. Finite element modeling results reinforce these findings, with local strength factor values without support ranging from 1.08-1.54 across the four openings. This study confirms that alteration type and the presence of geological structures are the primary factors controlling rock mass quality and support requirements at the Kencana underground mine.